Transexualidade, gênero e preconceito: Impasses e desafios na retificação do registro civil em Manaus-AM - (:unkn) unknown (Universidade Federal do Amazonas, 2018)
This study presupposes an aim of verifying the meaning of gender identity bias, interfering with the achievement of the transsexual subject, with regard to priorities. It is an innovative and little explored topic in Society Sciences. Transxuality is not related to a sexual preference, but to a gender identity of the subject. Gender identity involves a relationship with psychological and sexual development, as it refers to each person's being about and their sexuality, being able to identify with the sex in which the individual may be different from the sex. The subject does not identify with the biological sex nor with the social spaces that are taken by the society. Assume an orientation of the qualitative approaches without neglecting the quantitative requirements. The dynamic track of work should be accompanied by a follow-up interview. Among the multiple aspects observed, it was evident that the social name is not considered as a necessity for the recognition of the recognition of gender identity. The survey shows that the impasses still remain in the process of rectification of civil records by the judiciary. It should be concluded, finally, that this subject is heavily laden with prejudice, a fact that contributes to the non-rectification of the civil name by the copyright of the hand made by the Federal Supreme Court of Brazil.
Keywords: Identidade de Gênero; Gênero; Transexualidade; Direitos Sociais; CIÊNCIAS SOCIAIS APLICADAS: SERVIÇO SOCIAL